2015
DOI: 10.1002/jclp.22208
|View full text |Cite
|
Sign up to set email alerts
|

Current Trends in Theoretical Orientation of Psychologists: The Case of Quebec Clinicians

Abstract: Findings underline trends in Quebec clinical practice characterized by an increase in the number of psychologists identifying cognitive-behavioral approach as their primary self-reported theoretical orientation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…To a large extent, psychology training and practice have allied themselves with the medical-psychiatric paradigm, which in turn influences how professional psychologists understand, talk about, and relate to human suffering (Prilleltensky & Nelson, 2002). Although the medical-psychiatric paradigm has held a dominant position in professional psychology, alternative frameworks and orientations toward human suffering have been taken up within the field (Jaimes et al, 2015). Hence, a review of the range of perspectives among professional psychologists and among counselling psychology professionals specifically is warranted.…”
Section: Professional Psychologymentioning
confidence: 99%
See 2 more Smart Citations
“…To a large extent, psychology training and practice have allied themselves with the medical-psychiatric paradigm, which in turn influences how professional psychologists understand, talk about, and relate to human suffering (Prilleltensky & Nelson, 2002). Although the medical-psychiatric paradigm has held a dominant position in professional psychology, alternative frameworks and orientations toward human suffering have been taken up within the field (Jaimes et al, 2015). Hence, a review of the range of perspectives among professional psychologists and among counselling psychology professionals specifically is warranted.…”
Section: Professional Psychologymentioning
confidence: 99%
“…Several studies have revealed that Canadian counselling psychologists tend to identify with either one or an integration of the following orientations: psychodynamic, cognitive behavioural, existential-humanistic, feminist, postmodern, multicultural, and social justice (Gazzola et al, 2010;Jaimes et al, 2015;Ogunfowora & Drapeau, 2008;Sinacore et al, 2011). These differences may be attributed to multiple factors, including differences in graduate training and supervision, differences in workplace settings, and differences in context-bound views on psychological distress (Gazzola et al, 2010;Ogunfowora & Drapeau, 2008).…”
Section: Counselling Psychologistsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations into the practice of psychotherapy in the broader Canadian context are needed as the present data is focused on Quebec and may be difficult to translate to other settings. Quebec has a unique social and clinical context, with the most licensed psychologists in any province in Canada, a larger representation of those espousing a psychodynamic orientation (Jaimes, Larose-Hébert, & Moreau, 2015), lower psychotherapy fees compared with other provinces, and the requirement of functional bilingualism to become licensed. To gain a better understanding of independent practice across Canada, and attitudes toward favour-able models of government-funded mental health care, as well as any differences based on regional jurisdictions, further research is needed.…”
Section: Future Directionsmentioning
confidence: 99%